Work Motivation as a Mediator Between Quality Of Work Life, Organizational Communication, Work Discipline, Toward Employee Performance - Wahyuliati, Eka Ratna; Sukoco, Agus (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
The performance of health workers is very important because it is directly related to public health services in Surabaya, Indonesia. This research study aims to analyze the influence of quality of work life, organizational communication, and work discipline on employee performance with work motivation as an intervening variable at the Surabaya City Health Office. Research method a quantitative approach using the PLS-SEM. Data collection via questionnaires. The samples are 122 civil servants who work at the Surabaya Health Office. The analysis results show that work discipline and work motivation have a positive and significant effect on employee performance. Work discipline has a positive and significant effect on employee performance through work motivation as an intervening variable. Quality of work life and organizational communication do not have a significant effect, either directly or through work motivation as an intervening variable, on employee performance at the Surabaya City Health Office. This research found that work motivation is effective as a mediator in the relationship between work discipline and performance. This finding emphasizes the importance of improving discipline as a key strategy in strengthening motivation and driving employee performance. Meanwhile, strategies for improving organizational communication and the quality of work life need to be re-evaluated to be more effective in significantly influencing employee motivation and work results.